Work-nonwork conflict: an urgent situation for Brazilian women. Issue 1 (11th March 2021) - Oliveira, Érica Custódia de; Casado, Tania
Abstract : Purpose: Going further on a broad understanding of nonwork besides family, this study aims to analyze differences between women and men considering work-nonwork conflict (WNWC) in the Brazilian context, investigating time spent in eight nonwork dimensions and the dimensions more affected. Design/methodology/approach: The study was quantitative and descriptive. A survey was conducted, based on a validated WNWC scale. The sample consisted of 338 professionals working in Brazil. Data analysis was conducted through descriptive statistics and analysis of variance. Findings: Compared to men, women declare higher levels of WNWC considering the eight nonwork dimensions, present greater differences in stress-based conflicts and in more collective dimensions and have marriage or no children associated with more WNWC. Research limitations/implications: The study highlights the need to include more nonwork aspects into career and management studies to influence organizational practices and individual choices. The main limitation is the non-probabilistic sample (results not generalizable). Practical implications: Know more about WNWC will help organizations to improve lives by creating practices and a cultural environment to preserve women's and men's nonwork times. It may also help people to choose places to work for, matching their nonwork needs. Social implications: The study reinforces demands from new family arrangements, more couples in dual-career and an aging society: organizations must prepare to have workers that want or need to dedicate time to other interests besides family or children. Originality/value: It goes further on a broad understanding of nonwork besides family to understand WNWC and how it may affect differently men and women.